The regulatory role of PDE4B in the progression of inflammatory function study - Su, Yue; Ding, Jiaxiang; Yang, Fan; He, Cuixia; Xu, Yuanyuan; Zhu, Xingyu; Zhou, Huan; Li, Hongtao (Frontiers in Pharmacology, 2022)
Inflammation is a response of the body to external stimuli, and when the stimuli are persistent, they tend to trigger chronic inflammation. The presence of chronic inflammation is an important component of the tumor microenvironment produced by a variety of inflammatory cells. The relationship between chronic inflammation and cancer development has been widely accepted, and chronic inflammation has been associated with the development of many cancers, including chronic bronchitis and lung cancer, cystitis inducing bladder cancer, and chronic colorectitis patients susceptible to colorectal cancer, but the specific relationship and cellular mechanisms are still a hot topic of research. Recent studies have identified phosphodiesterase 4B (PDE4B), a member of the phosphodiesterase protein family, as a major cAMP metabolizing enzyme in inflammatory cells, and the therapeutic role of PDE4B as autoimmune diseases, chronic inflammation, etc., as well as attracted attention. In this review, we will present the tumors associated with chronic inflammation and the therapeutic role exhibited by PD4EB.